Evidence‐Based Medicine: The Design and Interpretation of Noninferiority Clinical Trials in Veterinary Medicine. (15th October 2013) - Freise, K.J.; Lin, T.‐L.; Fan, T.M.; Recta, V.; Clark, T.P.
<x xml:space="preserve">Abstract</x> Noninferiority trials are clinical studies designed to demonstrate that an investigational drug is at least as effective as an established treatment within a predetermined margin. They are conducted, in part, because of ethical concerns of administering a placebo to veterinary patients when an established effective treatment exists. The use of noninferiority trial designs has become more common in veterinary medicine with the increasing number of established veterinary therapeutics and the desire to eliminate potential pain or distress in a placebo‐controlled study. Selecting the appropriate active control and an a priori noninferiority margin between the investigational and active control drug are unique and critical design factors for noninferiority studies. Without reliable historical knowledge of the disease response in the absence of treatment and of the response to the selected active control drug, proper design and interpretation of a noninferiority trial is not possible. Despite the appeal of conducting noninferiority trials to eliminate ethical concerns of placebo‐controlled studies, there are real limitations and possible ethical conundrums associated with noninferiority trials. The consequences of incorrect study conclusions because of poor noninferiority trial design need careful attention. Alternative trial designs to typical noninferiority studies exist, but these too have limitations and must also be carefully considered.